Preliminary strontium isotope (87Sr/86Sr) baselines for the Bjäre Peninsula and Halland in southern Sweden - Macheridis, Stella; Sandstrom, Michael; Svensson, Andreas; Wilhelmson, Helene; Berggren, Åsa; Wranning, Per (Frontiers in Environmental Archaeology, 2024)
During the last decade, the application of strontium isotope analysis (87Sr/86Sr) has increased rapidly. The understanding of the strontium isoscape and the construction of a strontium isotope baseline in southern Scandinavia are biased toward Denmark and southwestern to eastern Scania. We report the results of new baseline samples in Halland and the Bjäre Peninsula, adding to the rich strontium isotope library that exists for southern Scandinavia. We add nuance to the previous divisions of Scania, in which the Bjäre Peninsula is not well represented. The results show that the Bjäre Peninsula is characterized by relatively low 87Sr/86Sr values gathered in the preliminary baseline 0.7100 ± 0.0024 (2σ, n = 8), similar to that of southwest Scania and Zealand in Denmark. There is a greater variation and higher values among the Halland samples. Together with previously published faunal samples, a preliminary 87Sr/86Sr baseline for Halland is 0.7122 ± 0.0055 (2σ, n = 24). We apply these baseline results to archaeological cases, both human and animal, from recent excavations in the Bjäre Peninsula. The results imply that there was a certain degree of mobility and interaction across the landscape in this region of southern Scandinavia in prehistory.